Studi Kasus Penerapan Metode RAD dalam Pengembangan Website Silsilah Keluarga Mbah Mansyur - Usep Saprudin; Maulana Rizki Pratama (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The study aims to develop a web-based family tree application using the Rapid Application Development (RAD) method for the Extended Family of Mbah Mansyur. RAD was chosen for its ability to accelerate the development process through rapid iterations and active user involvement. The application development was carried out in several cycles, incorporating user feedback to refine features and the interface. Testing results showed that the application effectively facilitates users in adding, editing, and viewing family data in real-time with responsive search functionality. The advantages of the RAD method were evident in the shorter development time and the application's adaptability to user needs. This application is expected to digitally preserve family history for future generations.